CUR VERBUM CAPAX HOMINIS: Alasan Inkarnasi Sabda menurut St. Thomas Aquinas (1225-1274) - Sinaga, Raidin (UNIKA Santo Thomas, 2008)
The absolute, infinite and holy God wants in the freedom of His love to communicate Himself to the world. This God’s self-communication has a history and subject. All christians believe that Jesus Christ is the supreme self-communication of God which takes place in the Incarnation. This is the central mystery of Christianity: the Triune God is made known to the world in Jesus Christ, the Second Person of the Trinity. He is the incarnate Logos of God. The doctrine of the incarnate Logos or the self-communication of God in the Second Person of the Trinity has generated many discussions and debates among Christians and Theologians, especially in the scholastic period: Cur Deus homo? Cur Verbum capax hominis? The answers given are based on biblical revelation (doctrine) or merely on human speculation (theologumenon). Thomas Aquinas is one of the great important figures on this debate.